Atmospheric blocking and winter mid-latitude climate variability - Davini, Paolo (Università Ca' Foscari Venezia, 2013)
Atmospheric blocking is a mid-latitude weather pattern that describes a quasi-stationary, long-lasting, high-pressure system that modifies the westerly flow, blocking (or at least di- verting) the eastward movement of the migratory cyclones. Blocking events can have major impacts on the mid-latitude weather, sometimes leading to extreme events as cold spells in winter or heat waves in summer. In this thesis, Northern Hemisphere winter blocking and its impacts on mid-latitude climate are analyzed through the introduction of a set of new bidimensional diagnostics based on the geopotential height that provide information about the occurrence, the duration, the intensity and the wave breaking associated with the block- ing. We are able to distinguish among three main categories of blocking: one placed at low latitudes over the Pacific and Atlantic oceans, unable to block or divert the flow. A second one is detected at high latitude occurring over Greenland and North Pacific, north of the jet stream and dominated by cyclonic wave breaking. Finally a third category is defined as the traditional mid-latitude blocking, and it appears as being only localized over Europe and driven by anticyclonic wave breaking. We address the relationship between the North Atlantic Oscillation (NAO) and the block- ing occurrence, showing that blocking over Greenland (Greenland Blocking, GB) is not only a key element to describe the NAO index, but it is essential also to modulate its pattern. Consistent with this, we link the eastward displacement of the NAO pattern observed in the recent years to the decreasing frequency of Greenland Blocking. On the other side, we notice that blocking events over Europe (European Blocking) are not correlated with the NAO. We also analyze the relationship between the Atlantic eddy driven jet stream dis- placements and blocking occurrence. We find that Greenland Blocking is linked with the equatorward displacements of the jet stream, while European Blocking is associated with poleward displacements of the ...